Data from: Modelling bat distributions and diversity in a mountain landscape using focal predictors in ensemble of small models - Scherrer, Daniel; Christe, Philippe; Guisan, Antoine (Dryad, 2020)
Aim: Bats are important components of mammalian biodiversity and strong bioindicators, but their fine scale distributions often remain less known than other taxa (e.g. plants, birds). Yet as highly mobile species with multiple needs in the landscape, bats impose serious modelling challenges, such as advanced use of neighbourhood analyses. The aims of this study were to test the use of a designed sampling of bats for biodiversity and conservation assessments, and to find appropriate modelling solutions for providing nature practitioners with reliable potential bat distribution maps in a mountain area of high conservation interest . Location: The western Swiss Alps of Vaud Methods: We conducted a one-year field survey combining passive acoustic recordings supplemented by mist net catching to collect data on bats. These data were then used to create univariate models with focal land use/cover variables using different focal window sizes to detect the optimal species specific scale of influence for each variable. The large number of selected variables was then used to create ensembles of small models at a 100mx100m resolution, and the resulting habitat suitability maps were transformed into species distribution maps for practitioners. Results: We were able to collect data to model 14 different bat species representing 66% of the Swiss bat diversity, including 4 red list species. In general, the most important variables were Euclidean distance to road or water, temperature and slope, but there was large variation among species both for the variable importance and the optimal focal window size. Main Conclusion: Our study greatly increased the knowledge of bats in this region and showed that many of the red list species are nowadays disappearing from the intensively used lowland plains and restricted to the remaining forests along the slopes . Additionally, we highlighted the importance of selecting the variable scale on a species specific basis accounting for their mobility and range sizes. Data used for modellingThis ...